Preparation method of mixed multistage full-spectrum efficient absorber based on phase separation technology

The mixed multi-stage plasmon resonance cavity is prepared through phase separation technology, which solves the problem of plasmon resonance cavity absorbing light energy in the limited wavelength range in the prior art, and realizes full-spectrum efficient absorption and simplified preparation process, which is suitable for large-scale production.

CN119805635AActive Publication Date: 2025-04-11NANJING TECH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411596821.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-04-11
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing plasmon resonance cavity absorbs light energy within a limited wavelength range, making it difficult to achieve efficient full spectrum absorption, and is complex in preparation and difficult to produce on a large scale.

Method used

A mixed multi-stage plasmon resonance cavity is prepared by phase separation technology, and a discontinuous mixed multi-stage structural template is formed through spin coating and reactive ion etching technology, and a gold layer is evaporated on its surface to achieve full spectrum response and high-efficiency light absorption.

Benefits of technology

It achieves efficient absorption of light energy within the full spectrum range, improves the utilization rate of sunlight, and simplifies the preparation process, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119805635A_ABST
    Figure CN119805635A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a mixed multistage plasmon resonant cavity based on a phase separation technology, and the method comprises the following steps: cleaning a substrate, carrying out the electron beam evaporation of a reflecting layer on the surface of the substrate, spin-coating a polymer layer and a silicon dioxide layer, and then coating a phase separation blended film, then selective etching is carried out through a reactive ion etching technology and then the PPSQ column is transmitted to a lower layer structure, the blend is exposed along with etching of oxygen and the PPSQ column, a few of small liquid drops are wrapped in the high-concentration blend, a film with nano holes is formed in a residual layer along with the increase of etching time, and the small column is etched out along with the increase of etching time; and then evaporating a gold layer on the template through an electron beam evaporation technology to obtain the mixed multi-stage multi-size plasmon resonant cavity. The mixed multistage resonant cavity provided by the invention has the advantages of high sunlight absorption, simple preparation method, stable performance, large-area production and the like, and can be compounded with a photocatalyst to improve the photocatalytic hydrogen production performance, provide more catalytic sites and improve the sunlight utilization rate. According to the invention, the multistage broadband plasmon resonant cavity is applied to the research of sunlight photocatalytic hydrogen production, and is of great significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of spectral absorption, and in particular to a method for preparing a hybrid multi-level plasmon resonance cavity based on a phase separation technology, and in particular to a method for preparing a plasmon resonance cavity for efficient absorption of the full spectrum of sunlight based on a phase separation technology. Background Art

[0002] In modern energy technology, solar energy is widely used in photocatalysis, photothermal conversion and other fields as a clean and renewable energy source. Therefore, broadening the absorption of solar light has received widespread attention in recent years. In order to improve the utilization efficiency of solar energy, researchers are committed to developing solar energy absorbing materials with high spectral absorption capabilities. Traditional solar absorbers can often only absorb light energy within a limited wavelength range, resulting in limited overall efficiency.

[0003] As a new type of optical structure, plasmon resonant cavity can produce a strong local electromagnetic field enhancement effect within a specific wavelength range, thereby improving the absorption efficiency of solar energy and is widely used in photocatalysis, photothermal conversion and other fields. However, a single plasmon resonant cavity is limited by the size of the structure, which is not conducive to wide-band and full-spectrum absorption. At present, through diversified regulation mechanisms, spectral regulation can be achieved to achieve wide-spectrum and high-efficiency light absorption. For example, by combining plasmon resonant cavity with other optical hierarchical structures [ACS Photonics, 2019, 6(1), 139–147]; preparing multi-mode optical resonant cavity composite plasmon surface (patent CN116165733A) can achieve enhanced light absorption effect in a wide spectral range. The plasmon resonance effect can significantly enhance the local electromagnetic field on the surface of the material, allowing it to absorb more light energy at a specific wavelength.

[0004] Hybrid multi-level plasmon resonant cavities can combine the advantages of different materials and structures to achieve a wider absorption spectrum range and higher absorption efficiency. At the same time, by rationally designing and optimizing the structural parameters of the plasmon resonant cavity, the spectral response range can be further improved, and its overall energy conversion efficiency can also be improved, providing a new way for the efficient use of solar energy. However, the more scales the structure has, the more complex the design is, which increases the difficulty of preparation. Therefore, for comprehensive considerations of structural performance, process convenience and other aspects, it is very necessary to design a hybrid multi-level structure with a simple preparation method and good compatibility with conventional micro-nano processes. Summary of the invention

[0005] The purpose of the present invention is to solve the above technical problems and provide a method for preparing a hybrid multi-level plasmon resonant cavity based on phase separation technology.

[0006] The technical solution of the present invention is a method for preparing a hybrid multi-level plasmon resonant cavity based on phase separation technology, and the specific steps are as follows:

[0007] a) Substrate cleaning: The glass substrate was ultrasonically cleaned in an ethanol solution, and finally rinsed with deionized water, dried with nitrogen, and dried on a hot plate;

[0008] b) Depositing a metal layer: depositing a reflective metal layer on the substrate using electron beam evaporation or resistance evaporation technology;

[0009] c) spin coating an organic solution containing no silicon polymer on the surface of the deposited reflective metal layer, and obtaining a layer containing no silicon polymer after curing;

[0010] d) depositing a SiO2 film on the silicon-free polymer layer;

[0011] e) dissolving polystyrene and silicon-containing polymer in an organic solvent and stirring to form a mixed phase separation solution;

[0012] f) spin coating the blended phase separation solution on the substrate prepared in step d) to obtain a phase separation blended thin film;

[0013] g) selectively etching the phase separation blend film using reactive ion etching technology to form a discontinuous hybrid multi-level structure template on the surface of the substrate;

[0014] h) Using electron beam evaporation technology to evaporate a layer of gold on the surface of the template.

[0015] Preferably, the substrate in step a) is silicon, quartz or glass.

[0016] Preferably, the metal layer in step b) is gold, silver or aluminum; and its thickness is 50-100 nm.

[0017] Preferably, the organic solution containing no silicon polymer in step c) is a chlorobenzene solution of polymethyl methacrylate with a mass concentration of 1% to 5%; the thickness of the silicon-free polymer layer is 100-500nm; the spin coating speed is 1000-4000 rpm and the spin coating time is 40-60s.

[0018] Preferably, the curing temperature in step c) is 80-85° C. and the curing time is 1-3 min.

[0019] Preferably, the method for depositing the SiO2 layer in step d) is plasma enhanced chemical vapor deposition technology (OXFORD P80 PECVD); the thickness of the deposited SiO2 layer is 15-40 nm.

[0020] Preferably, the organic solvent in step e) is toluene or chlorobenzene; the silicon-containing polymer is polyphenylsilsesquioxane; the mass ratio of polystyrene to silicon-containing polymer is (1-5):1; and the total mass concentration of the mixed phase separation solution is 2-10%.

[0021] Preferably, the spin coating speed in step f) is 2000-4000 rpm, and the spin coating time is 40-60 s.

[0022] The reactive ion etching technology instrument described in the preferred step g) is an ULVAC ICPRIE etcher; the selective etching process is: first, use O2 plasma to etch away part of the continuous phase of polystyrene to form a dispersed phase of polyphenylsilsesquioxane of the nanocolumns, and the etching time is 250-500s; then use O2 / CHF3 mixed gas to etch away part of the polyphenylsilsesquioxane remaining at the bottom of the nanocolumns, and the etching time is 20-250s; then use this as a mask, continue to use CF4 / CHF3 mixed gas to etch down the SiO2 layer, and the etching time is 90-210s, and then use O2 plasma to etch down the silicon-free polymer layer, and the etching time is 50-250s; the plasma flow rate is 10-30sccm, and the power is 35-40W.

[0023] The electron beam evaporation process in step h) is preferably as follows: venting air into the coating apparatus to break the vacuum state, clamping the template on the sample table, adding metal nickel vapor to the tungsten crucible below, and evacuating until the vacuum degree is 1-5*10 -3 Pa, turn on the high-voltage electron beam, evaporate a 10-20nm metal gold layer, and the coating rate is

[0024]

[0025] Beneficial effects:

[0026] The present invention provides a hybrid multi-level disordered plasmon resonant cavity prepared based on phase separation technology. The prepared resonant cavity can respond in the full spectrum range and has strong light absorption. At the same time, plasmons will generate hot electrons to enhance the electric field strength. After compounding with a photocatalyst, it can effectively promote the separation of photogenerated electrons and holes, thereby promoting photocatalytic hydrogen production performance and improving the utilization rate of sunlight. In addition, the preparation process of the present invention is simple, suitable for large-area preparation, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the structure of the hybrid multi-level plasmon resonant cavity of the present invention.

[0028] Figure 2 This is a SEM image of the hybrid multi-stage resonant cavity of Example 1 of the present invention.

[0029] Figure 3 This is a cross-sectional SEM image of the hybrid multi-stage resonant cavity of Example 1 of the present invention.

[0030] Figure 4 This is an absorption spectrum diagram of the hybrid multi-stage resonant cavity prepared by phase separation technology in Example 1 of the present invention at 200-2500nm.

[0031] Figure 5 This is a SEM image of the hybrid multi-stage resonant cavity of Example 2 of the present invention.

[0032] Figure 6 This is an absorption spectrum diagram of the hybrid multi-stage resonant cavity prepared by phase separation technology in Example 2 of the present invention at 200-2500nm. DETAILED DESCRIPTION

[0033] The specific implementation modes of the present invention are described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, but not all of the embodiments.

[0034] The structural schematic diagram of the hybrid multi-level plasmon resonant cavity of Examples 1-5 of the present invention is as follows Figure 1 shown.

[0035] In the following embodiments, the substrate cleaning is as follows: the glass substrate is ultrasonically cleaned in an ethanol solution, and finally cleaned with deionized water, dried with nitrogen, and dried on a hot plate;

[0036] The electron beam evaporation process involved in step h) of the following embodiments is as follows: venting the gas in the coating apparatus to break the vacuum state, clamping the above template on the sample table, adding metal nickel vapor material to the tungsten crucible below, and evacuating until the vacuum degree is 1-5*10 -3 Pa, turn on the high-voltage electron beam, evaporate a 10-20nm metal gold layer, and the coating rate is

[0037] In the following examples, when testing the photochemical performance, a photocatalyst film is deposited by chemical bath or electrostatic adsorption in the prepared multi-level plasmon resonant cavity. The photocatalytic film is cadmium sulfide, and the deposition time is 10-30 minutes.

[0038] Example 1

[0039] Depositing metal layer: Using electron beam evaporation technology to deposit a 50nm metal layer of gold on the glass substrate;

[0040] A polymethyl methacrylate polymer layer was prepared on the surface of a glass substrate: a polymethyl methacrylate solution with a mass fraction of 3% was prepared using chlorobenzene as a solvent, and the solution was spin-coated on the glass substrate with a gold deposited metal layer at a speed of 2000 rpm for 45 seconds, and then cured by heat treatment at 85°C for 3 minutes. The thickness of the polymethyl methacrylate was 200 nm.

[0041] Deposition of SiO2 layer: A SiO2 layer with a thickness of 20 nm is deposited on the polymer layer using chemical vapor deposition technology;

[0042] Preparation of a phase separation structure film: spin coating a blended polymer and solution of polystyrene and polyphenylsilsesquioxane on the above substrate, wherein the mass ratio of polystyrene to polyphenylsilsesquioxane is 1:1, the total solution concentration is 6%, the solvent is toluene, the spin coating rate of the blended polymer solution is 3000 rpm, and the spin coating time is 45 s;

[0043] Selective etching: O2 plasma (30sccm, 35W) was used to etch for 400s to remove the polystyrene continuous phase, and then O2 / CHF3 mixed gas (20sccm / 20sccm, 40W) was used to etch for 120s to partially remove the residual polyphenylsilsesquioxane adhering to the bottom of the nanopillars, forming a film with nanopores on the glass substrate, accompanied by the appearance of residual layer small pillars. Using this as a mask, CF4 / CHF3 mixed gas was used to etch downward for 130s to remove the SiO2 layer in the pores, and then O2 plasma (10sccm, 35W) was used to etch downward for 100s to remove the polymethyl methacrylate polymer layer under the pores to obtain a nanopore phase separation template;

[0044] Coating: Electron beam evaporation technology was used to coat a 15 nm gold film on the above substrate to produce a multi-level plasmon resonant cavity; the coating rate was The vacuum degree during coating is 1*10 -3 Pa; SEM images of the hybrid multi-stage resonant cavity are shown in Figure 2 The corresponding cross-sectional electron microscope image is shown in Figure 3 As shown in the figure, the ultraviolet absorption spectrum of the plasmon resonant cavity was tested. Figure 4 As shown, it is shown that the multi-level plasmon resonant cavity has high absorption efficiency in the range of 200-2500nm;

[0045] Cadmium sulfide was deposited by chemical bath deposition, and the photocatalyst film was uniformly loaded on the surface of the multi-level structure. The deposition time was 20 minutes, and a uniformly mixed multi-level resonant cavity photocatalytic film was obtained; the above sample was placed in a 200 mg / mL glucose solution for photocatalytic hydrogen production experiments. The photocatalytic decomposition of water and hydrogen evolution test was carried out using an online sampling system connected to a gas chromatograph (7890B, Agilent, with argon as the carrier gas), in which a thermal conductivity detector (TCD) was used. Under the irradiation of a 300W xenon lamp, the air in the reactor was removed by blowing argon for 1 hour to deoxygenate the system, and then the hydrogen production was recorded every 30 minutes. After testing for 2 hours, the photocatalytic yield can reach 8.94μmol.

[0046] Example 2

[0047] Depositing metal layer: Using electron beam evaporation technology to deposit a 100nm metal layer of gold on the glass substrate;

[0048] Prepare a polymethyl methacrylate polymer layer on the surface of a glass substrate: use chlorobenzene as a solvent to prepare a polymethyl methacrylate solution with a mass fraction of 3%, spin-coat it on the glass substrate with the metal layer deposited, the rotation speed is 2000 rpm, the spin-coating time is 50s, and the curing is completed by heat treatment at 85°C for 2min. The thickness of the polymethyl methacrylate is 200nm;

[0049] Deposition of SiO2 layer: A SiO2 layer with a thickness of 20 nm is deposited on the polymer layer using chemical vapor deposition technology;

[0050] Preparation of a phase separation structure film: spin coating a blended polymer and solution of polystyrene and polyphenylsilsesquioxane on the above substrate, wherein the mass ratio of polystyrene to polyphenylsilsesquioxane is 1:1, the total solution concentration is 10%, the solvent is toluene, the spin coating rate of the blended polymer solution is 3000 rpm, and the spin coating time is 50 s;

[0051] Selective etching: Use O2 plasma (10sccm, 35W) to etch for 500s to remove the polystyrene continuous phase, then use O2 / CHF3 mixed gas (20sccm / 20sccm, 40W) to etch for 250s to partially remove the residual polyphenylsilsesquioxane adhering to the bottom of the nanocolumns, forming a film with nanopores on the glass substrate, accompanied by the appearance of residual layer small pillars, and then use CF4 / CHF3 mixed gas to etch downward for 130s using this as a mask to remove the SiO2 layer in the pores, and then use O2 plasma (10sccm, 35W) to etch downward for 100s to remove the polymethyl methacrylate polymer layer under the pores to obtain a nanopore phase separation template;

[0052] Coating: Electron beam evaporation technology was used to coat a 10 nm gold film on the above substrate to produce a multi-level plasmon resonant cavity; the coating rate was The vacuum degree during coating is 2*10 -3 Pa; SEM images of the hybrid multi-stage resonant cavity are shown in Figure 5 As shown in the figure, the ultraviolet absorption spectrum of the plasmon resonant cavity was tested. Figure 6 As shown, it is shown that the multi-level plasmon resonant cavity can absorb sunlight in the range of 200-2500nm very well;

[0053] Cadmium sulfide was deposited by chemical bath deposition, and the photocatalyst film was uniformly loaded on the surface of the multi-level structure. The deposition time was 30 minutes, and a uniformly mixed multi-level resonant cavity photocatalytic film was obtained; the above sample was placed in a 200 mg / mL glucose solution for photocatalytic hydrogen production experiments. The photocatalytic decomposition of water and hydrogen evolution test was carried out using an online sampling system connected to a gas chromatograph (7890B, Agilent, with argon as the carrier gas), in which a thermal conductivity detector (TCD) was used. Under the irradiation of a 300W xenon lamp, the air in the reactor was removed by blowing argon for 1 hour to deoxygenate the system, and then the hydrogen production was recorded every 30 minutes. After testing for 2 hours, the photocatalytic yield can reach 8.54μmol.

[0054] Example 3

[0055] Depositing metal layer: Using electron beam evaporation technology to deposit a 50nm silver metal layer on the silicon wafer;

[0056] Prepare a polymethyl methacrylate polymer layer on the surface of a silicon wafer: use chlorobenzene as a solvent to prepare a polymethyl methacrylate solution with a mass fraction of 1%, spin-coat it on the silicon substrate with the deposited metal layer of silver, the rotation speed is 2000 rpm, the spin-coating time is 40s, and the curing is completed by heat treatment at 85°C for 2min. The thickness of the polymethyl methacrylate is 100nm;

[0057] Deposition of SiO2 layer: A SiO2 layer with a thickness of 40 nm is deposited on the polymer layer using chemical vapor deposition technology;

[0058] Preparation of a phase separation structure film: spin coating a blended polymer and solution of polystyrene and polyphenylsilsesquioxane on the above substrate, wherein the mass ratio of polystyrene to polyphenylsilsesquioxane is 3:1, the total solution concentration is 2%, the solvent is chlorobenzene, the spin coating rate of the blended polymer solution is 4000 rpm, and the spin coating time is 60 s;

[0059] Selective etching: Use O2 plasma (10sccm, 35W) to etch for 250s to remove the polystyrene continuous phase, then use O2 / CHF3 mixed gas (20sccm / 20sccm, 40W) to etch for 20s to partially remove the residual polyphenylsilsesquioxane adhering to the bottom of the nanopillars, forming a film with nanopores on the silicon wafer substrate, while exposing the upper small-sized pillars, and then use CF4 / CHF3 mixed gas to etch downward for 210s using this as a mask to remove the SiO2 layer in the pores, and then use O2 plasma (30sccm, 35W) to etch downward for 50s to remove the polymethyl methacrylate polymer layer under the pores, and obtain a multi-level and multi-size phase separation template;

[0060] Coating: Electron beam evaporation technology was used to coat a 15 nm gold film on the above substrate to produce a multi-level plasmon resonant cavity; the coating rate was The vacuum degree during coating is 5*10 -3 Pa; the multi-level plasmon resonant cavity has high absorption efficiency in the range of 200-2500nm.

[0061] Cadmium sulfide was deposited by chemical bath deposition, and the photocatalyst film was uniformly loaded on the surface of the multi-level structure. The deposition time was 20 minutes, and a uniformly mixed multi-level resonant cavity photocatalytic film was obtained; the above sample was placed in a 200 mg / mL glucose solution for photocatalytic hydrogen production experiments. The photocatalytic decomposition of water and hydrogen evolution test was carried out using an online sampling system connected to a gas chromatograph (7890B, Agilent, with argon as the carrier gas), in which a thermal conductivity detector (TCD) was used. Under the irradiation of a 300W xenon lamp, the air in the reactor was removed by blowing argon for 1 hour to deoxygenate the system, and then the hydrogen production was recorded every 30 minutes. After testing for 2 hours, the photocatalytic yield can reach 6.91μmol.

[0062] Example 4

[0063] Depositing metal layer: Using electron beam evaporation technology to deposit a 50nm metal layer of gold on the silicon wafer;

[0064] Prepare a polymer layer on the surface of the silicon wafer: use chlorobenzene as solvent, prepare a polymethyl methacrylate solution with a mass fraction of 5%, spin-coat it on the silicon substrate with the deposited metal layer, the rotation speed is 1200 rpm, the spin-coating time is 60s, and the curing is completed by heat treatment at 80℃ for 1min. The thickness of the polymethyl methacrylate is 500nm;

[0065] Deposition of SiO2 layer: A SiO2 layer with a thickness of 15 nm is deposited on the polymer layer using chemical vapor deposition technology;

[0066] Preparation of a phase separation structure film: spin coating a blended polymer and solution of polystyrene and polyphenylsilsesquioxane on the above substrate, wherein the mass ratio of polystyrene to polyphenylsilsesquioxane is 5:1, the total solution concentration is 6%, the solvent is toluene, the spin coating rate of the blended polymer solution is 2000 rpm, and the spin coating time is 40 s;

[0067] Selective etching: Use O2 plasma (10sccm, 35W) to etch for 400s to remove the polystyrene continuous phase, then use O2 / CHF3 mixed gas (20sccm / 20sccm, 40W) to etch for 250s to remove the residual polyphenylsilsesquioxane adhering to the bottom of the nanopillars, forming a nanopillar film on the silicon wafer substrate, and then use CF4 / CHF3 mixed gas as a mask to continue to etch downward for 90s to remove the SiO2 layer in the hole, and then use O2 plasma (10sccm, 35W) to etch downward for 250s to remove the polymethyl methacrylate polymer layer under the hole to obtain a nanoporous phase separation template;

[0068] Coating: Electron beam evaporation technology was used to coat a 20 nm gold film on the above substrate to produce a multi-level plasmon resonant cavity; the coating rate was The vacuum degree during coating is 2*10 -3 Pa; the multi-level plasmon resonant cavity has high absorption efficiency in the range of 200-2500nm.

[0069] Composite photocatalyst: Cadmium sulfide was deposited by chemical bath deposition, and the photocatalyst film was uniformly loaded on the surface of the multi-level structure. The deposition time was 30 minutes to obtain a uniformly mixed multi-level resonant cavity photocatalytic film; the above sample was placed in a 200 mg / mL glucose solution for photocatalytic hydrogen production experiments. The photocatalytic decomposition of water and hydrogen evolution test was carried out using an online sampling system connected to a gas chromatograph (7890B, Agilent, with argon as carrier gas), in which a thermal conductivity detector (TCD) was used. Under the irradiation of a 300W xenon lamp, the air in the reactor was removed by blowing argon for 1 hour to deoxygenate the system, and then the hydrogen production was recorded every 30 minutes. The test was carried out for 2 hours, and the photocatalytic yield could reach 7.74μmol.

[0070] Example 5

[0071] Depositing metal layer: Using electron beam evaporation technology to deposit a metal layer of aluminum 100nm on the glass substrate;

[0072] Prepare a polymethyl methacrylate polymer layer on the surface of a glass substrate: use chlorobenzene as a solvent to prepare a polymethyl methacrylate solution with a mass fraction of 3%, spin-coat it on the glass substrate with the deposited metal layer aluminum, the rotation speed is 4000 rpm, the spin-coating time is 45s, and the curing is completed by heat treatment at 85°C for 3min. The thickness of the polymethyl methacrylate is 200nm;

[0073] Deposition of SiO2 layer: A SiO2 layer with a thickness of 30 nm is deposited on the polymer layer using chemical vapor deposition technology;

[0074] Preparation of a phase separation structure film: spin coating a blended polymer and solution of polystyrene and polyphenylsilsesquioxane on the above substrate, wherein the mass ratio of polystyrene to polyphenylsilsesquioxane is 1:1, the total solution concentration is 6%, the solvent is toluene, the spin coating rate of the blended polymer solution is 2000 rpm, and the spin coating time is 40 s;

[0075] Selective etching: O2 plasma (10sccm, 35W) was used to etch for 400s to remove the polystyrene continuous phase, and then O2 / CHF3 mixed gas (20sccm / 20sccm, 40W) was used to etch for 120s to remove the residual polyphenylsilsesquioxane adhering to the bottom of the nanopillars, forming a film with nanopores on the glass substrate, accompanied by smaller pillars that appeared as the etching time increased. Using this as a mask, CF4 / CHF3 mixed gas was used to etch downward for 180s to remove the SiO2 layer in the pores, and then O2 plasma (30sccm, 35W) was used to etch downward for 100s to remove the polymethyl methacrylate polymer layer under the pores to obtain a nanopore phase separation template;

[0076] Coating: Electron beam evaporation technology was used to coat a 10 nm gold film on the above substrate to produce a multi-level plasmon resonant cavity; the coating rate was The vacuum degree during coating is 3*10 -3 Pa; the multi-level plasmon resonant cavity has high absorption efficiency in the range of 200-2500nm;

[0077] Cadmium sulfide was deposited by chemical bath deposition, and the photocatalyst film was uniformly loaded on the surface of the multi-level structure. The deposition time was 20 minutes, and a uniformly mixed multi-level resonant cavity photocatalytic film was obtained; the above sample was placed in a 200 mg / mL glucose solution for photocatalytic hydrogen production experiments. The photocatalytic decomposition of water and hydrogen evolution test was carried out using an online sampling system connected to a gas chromatograph (7890B, Agilent, with argon as the carrier gas), in which a thermal conductivity detector (TCD) was used. Under the irradiation of a 300W xenon lamp, the air in the reactor was removed by blowing argon for 1 hour to deoxygenate the system, and then the hydrogen production was recorded every 30 minutes. After testing for 2 hours, the photocatalytic yield can reach 8.71μmol.

Claims

1. A method for preparing a hybrid multi-level plasmon resonant cavity based on phase separation technology, the specific steps of which are as follows: a) Substrate cleaning: The glass substrate was ultrasonically cleaned in an ethanol solution, and finally rinsed with deionized water, dried with nitrogen, and dried on a hot plate; b) Depositing a metal layer: depositing a reflective metal layer on the substrate using electron beam evaporation or resistance evaporation technology; c) spin coating an organic solution containing no silicon polymer on the surface of the deposited reflective metal layer, and obtaining a layer containing no silicon polymer after curing; d) depositing a SiO2 film on the silicon-free polymer layer; e) dissolving polystyrene and silicon-containing polymer in an organic solvent and stirring to form a mixed phase separation solution; f) spin coating the blended phase separation solution on the substrate prepared in step d) to obtain a phase separation blended thin film; g) selectively etching the phase separation blend film using reactive ion etching technology to form a discontinuous hybrid multi-level structure template on the surface of the substrate; h) Using electron beam evaporation technology to evaporate a layer of gold on the surface of the template.

2. The method according to claim 1, characterized in that In step a), the substrate is silicon, quartz or glass.

3. The method according to claim 1, characterized in that The metal layer in step b) is gold, silver or aluminum; its thickness is 50-100 nm.

4. The method according to claim 1, characterized in that: The organic solution containing no silicon polymer in step c) is a chlorobenzene solution of polymethyl methacrylate with a mass concentration of 1% to 5%; the thickness of the silicon-free polymer layer is 100-500nm; the spin coating speed is 1000-4000 rpm and the spin coating time is 40-60s.

5. The method according to claim 1, characterized in that The curing temperature in step c) is 80-85° C. and the curing time is 1-3 minutes.

6. The method according to claim 1, characterized in that The method for depositing the SiO2 layer in step d) is plasma enhanced chemical vapor deposition technology; the thickness of the deposited SiO2 layer is 15-40nm.

7. The method according to claim 1, characterized in that The organic solvent in step e) is toluene or chlorobenzene; the silicon-containing polymer is polyphenylsilsesquioxane; the mass ratio of polystyrene to the silicon-containing polymer is (1-5):1; and the total mass concentration of the mixed phase separation solution is 2-10%.

8. The method according to claim 1, characterized in that In step f), the rotation speed of the spin coating is 2000-4000 rpm, and the spin coating time is 40-60s.

9. The method according to claim 1, characterized in that: The reactive ion etching technology instrument described in step g) is an ULVAC ICPRIE etcher; the selective etching process is: first, use O2 plasma to etch away part of the continuous phase of polystyrene to form a dispersed phase of polyphenylsilsesquioxane of the nanocolumns, and the etching time is 250-500s; then use O2 / CHF3 mixed gas to etch partially remove the residual polyphenylsilsesquioxane adhered to the bottom of the nanocolumns, and the etching time is 20-250s; then use this as a mask, continue to etch the SiO2 layer downward with CF4 / CHF3 mixed gas, and the etching time is 90-210s, and then use O2 plasma to etch downward the silicon-free polymer layer, and the etching time is 50-250s; the plasma flow rate is 10-30sccm, and the power is 35-40W.

10. The method according to claim 1, characterized in that The electron beam evaporation process described in step h) is as follows: venting air into the coating apparatus to break the vacuum state, clamping the above template on the sample table, adding metal nickel vapor material to the tungsten crucible below, and evacuating until the vacuum degree is 1-5*10 -3 Pa, turn on the high-voltage electron beam, evaporate a 10-20nm metal gold layer, and the coating rate is

Citation Information

Patent Citations

  • Five-layer nano material ultra-wideband perfect absorber and preparation method thereof

    CN113009606A

  • Multi-mode optical resonant cavity composite plasmon surface and preparation method thereof

    CN116165733A

  • Preparation method of photoelectrochemical weak light detection film

    CN116678496A

  • Method of forming multiple nanopatterns and method of manufacturing organic solar cell using the same

    US20180083190A1